2016
DOI: 10.1111/apm.12496
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutases in chronic gastritis

Abstract: Human gastric diseases have shown significant changes in the activity and expression of superoxide dismutase (SOD) isoforms. The aim of this study was to detect Mn-SOD activity and expression in the tissue of gastric mucosa, primarily in chronic gastritis (immunohistochemical Helicobacter pylori-negative gastritis, without other pathohistological changes) and to evaluate their possible connection with pathohistological diagnosis. We examined 51 consecutive outpatients undergoing endoscopy for upper gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The likely reason is that long-term retention and stimulation of hard faeces causes inflammation in the intestinal tract [29]. Mn-SOD can reduce the activity under inflammation [30]. SOD can transform harmful superoxide radicals into hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…The likely reason is that long-term retention and stimulation of hard faeces causes inflammation in the intestinal tract [29]. Mn-SOD can reduce the activity under inflammation [30]. SOD can transform harmful superoxide radicals into hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…pylori-infected individuals with moderate to severe gastric mucosa inflammation present greater expression of Mn-SOD than individuals with the intact gastric mucosa. Mn-SOD expression was observed to be more enhanced primarily within the pit cells of the antrum and not the corpus [122]. It was reported that exposure to the CagA-positive H. pylori strains results in significantly greater SOD, catalase, and glutathione peroxidase activities compared to exposure to the CagA-negative strains [123].…”
Section: Superoxidase Dismutasementioning
confidence: 93%
“…These inflammatory mediators could recruit and activate inflammatory cells, such as neutrophils and macrophages, to amplify inflammation [ 16 ]. MPO and SOD1 were involved in the oxidative stress [ 17 ]. PTGS1 and PTGS2 were related with prostaglandin, which is an important hormone in immune regulation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%